Evaluation of the efficacy of neonicotinoid and pyrethroid insecticides in Diaphorina citri Kuwayama (Hemiptera: Liviidae) populations in Colombia - Ramírez-Godoy, Augusto; Puentes-Pérez, Gina; Restrepo-Díaz, Hermann (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The Asian citrus psyllid Diaphorina citri is the insect vector of the disease known as huanglongbing (HLB), which is the most devastating disease of citrus crops in the world. The Asian citrus psyllid was officially reported in Colombia in 2007, and a national phytosanitary emergency was declared because of the presence of HLB in 2015. Two different experiments were carried out in two locations (Apulo and Jerusalén, Department of Cundinamarca) in Colombia to evaluate the effectiveness of neonicotinoid (clothianidin, imidacloprid and thiamethoxan) and pyrethroid applications (bifenthrin, deltamethrin and lambda cyhalothrin) on the control of D. citri populations (adults, nymphs and eggs) in ‘Tahiti’ lime trees established under tropical dry forest conditions. In the first experiment, trees were foliarly treated as follows: (1) untreated trees; (2) trees treated with 100 g ha-1 of imidacloprid; (3) trees treated with 60 g ha-1 of bifenthrin; (4) trees treated with 12.5 g ha-1 of deltamethrin and (5) trees treated with a co-formulation of 70 g ha-1 of a neonicotinoid (thiametoxan) and 53 g ha-1 of a pyrethroid (lambda cyhalothrin). In the second experiment, trees were treated with 100 g ha-1 of clothianidin. Foliar insecticide applications were carried out at 0 and 4 weeks after the initiation of treatments (WAT). In the first trial, the control presented a mean number of individuals per flush of ≈1.14, whereas the trees treated with neoinicotinoids and pyrethroids showed 50% fewer individuals (0.53-0.61). For the population of immatures, the number of nymphs was 2.25 nymphs per flush in the control, as compared to 0.82-1.22 individuals observed in the treatments with insecticides. The mean number of eggs was also between 80-100% higher in the control trees (2.37 individuals), as compared to the treated trees (1.14-1.78). In the second trial, the use of clothianidin showed a higher control of eggs. The results suggest that the rotation of neonicotinoids with pyrethroids can be a tool to reduce populations and delay resistance processes in D. citri in citrus trees established under tropical dry forest conditions in Colombia.